Seroprevalence, distribution, and risk factors for human leptospirosis in the United States Virgin Islands. - Aileen Artus; Ilana J Schafer; Caitlin M Cossaboom; Dana L Haberling; Renee Galloway; Graham Sutherland; A Springer Browne; Joseph Roth; Valicia France; Hannah M Cranford; Kristine J Kines; Justine Pompey; et al. (PLoS Neglected Tropical Diseases, 2022)
Background The first documented human leptospirosis cases in the U.S. Virgin Islands (USVI) occurred following 2017 Hurricanes Irma and Maria. We conducted a representative serosurvey in USVI to estimate the seroprevalence and distribution of human leptospirosis and evaluate local risk factors associated with seropositivity. Methodology/principal findings A stratified, two-stage cluster sampling design was used and consisted of three island strata and random selection of census blocks and then households. All eligible members of selected households were invited to participate (≥5 years old, resided in USVI ≥6 months and ≥6 months/year). Household and individual-level questionnaires were completed, and serum collected from each enrolled individual. Microscopic agglutination test serology was conducted, and bivariate and logistic regression analyses completed to identify risk factors for seropositivity. In March 2019, 1,161 individuals were enrolled from 918 households in St. Croix, St. Thomas, and St. John. The territory-wide weighted seroprevalence was 4.0% (95% CI:2.3-5.7). Characteristics/exposures independently associated with seropositivity using logistic regression included contact with cows (OR: 39.5; 95% CI: 9.0-172.7), seeing rodents/rodent evidence or contact with rodents (OR: 2.6; 95% CI: 1.1-5.9), and increasing age (OR: 1.02; 95% CI: 1.002-1.04); full or partial Caucasian/White race was negatively correlated with seropositivity (OR: 0.02, 95% CI: 0.04-0.7). Bivariate analysis showed self-reported jaundice since the 2017 hurricanes (pRR: 5.7; 95% CI: 1.0-33.4) was associated with seropositivity and using a cover/lid on cisterns/rainwater collection containers (pRR: 0.3; 95% CI: 0.08-0.8) was protective against seropositivity. Conclusions/significance Leptospirosis seropositivity of 4% across USVI demonstrates an important human disease that was previously unrecognized and emphasizes the importance of continued leptospirosis surveillance and investigation. Local risk factors identified may help guide future human and animal leptospirosis studies in USVI, strengthen leptospirosis public health surveillance and treatment timeliness, and inform targeted education, prevention, and control efforts.